THE INDICATOR OF THE USE OF VERBAL AND NON-VERBAL FORMS OF COMMUNICATION IN THE SPEECH ETIQUETTE OF CONDOLENCES IN ENGLISH AND UZBEK - Narmurodova Gulnoza Ilhom Kizi (Journals Park Publishing, 2023)
Language is an integral part of the culture, lifestyle, and nation of the region where people live. The cultural values, worldviews, customs, and traditions of the society are preserved in written and oral form and transmitted to the whole world community through the medium of language. The relevance of studying this topic is to improve the effectiveness of learning and learning about the uniqueness of the English language and English national culture, the communication culture of the nation, and speech etiquette by modeling the real communicative situation of condolence.
Keywords: language and culture, verbal and non-verbal communication, Christianity, Islam, emotional appeals, condolence, speech etiquette.